(untitled) (TAJ: Journal of Teachers Association, 2018)
Objectives: To determine the BMI status of the students of Rajshahi Islami Bank Medical College and to calculate frequency of different BMI categories Methodology: A cross-sectional questionnaire based study was carried out in medical students of Rajshahi Islami Bank Medical College, Rajshahi. Body weight and height were measured and body mass index (BMI) values were calculated by dividing weight with (height) 2. Overweight and obesity were defined using WHO international standard BMI cut-offs. Results: The overall prevalence of underweight students was 29.9% out of which 9.6% fell under the category of severely underweight (BMI of <16.5). In overweight category there were 8%. The frequency of students falling in Obese Class I, II & III was 2.7%, 0.6% & 0.0% respectively. It was found that more female students compared to male students were underweight. In the overweight and obese categories there was a preponderance of male students. A positive correlation was found between perception of obesity amongst parents and overweight obese students. Conclusion: According to this study, underweight, especially in girls, should be considered a serious health problem among adolescent students which needs to be addressed. Obesity on the other hand does not seem to be a major issue amongst them. TAJ 2014; 27(2): 1-5